A simulation study of a printed circuit board assembly line - 423898 Loh, Chee Yeh; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal (Skudai, Johor : Penerbit UTM, 2007)
Includes bibliographical references